2016
DOI: 10.1111/1365-2664.12608
|View full text |Cite
|
Sign up to set email alerts
|

Modest enhancements to conventional grassland diversity improve the provision of pollination services

Abstract: Summary Grassland for livestock production is a major form of land use throughout Europe and its intensive management threatens biodiversity and ecosystem functioning in agricultural landscapes. Modest increases to conventional grassland biodiversity could have considerable positive impacts on the provision of ecosystem services, such as pollination, to surrounding habitats.Using a field‐scale experiment in which grassland seed mixes and sward management were manipulated, complemented by surveys on working far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 44 publications
(77 reference statements)
3
89
0
Order By: Relevance
“…For example, a recent study found that increasing plant species richness was positively associated with increased pollinator functional diversity and with several other metrics of pollination services (Orford et al . ).…”
Section: Biodiversity‐dependent Agroecosystem Servicesmentioning
confidence: 97%
“…For example, a recent study found that increasing plant species richness was positively associated with increased pollinator functional diversity and with several other metrics of pollination services (Orford et al . ).…”
Section: Biodiversity‐dependent Agroecosystem Servicesmentioning
confidence: 97%
“…Sowing Trifolium species increased bee abundance (Power and Stout, 2011). Even a modest increase in conventional grassland plant diversity with legumes and forbs enhances pollinator functional diversity, richness, and abundance, improving pollination services and crop and wildflower reproduction (Orford et al, 2016). However, some rare pollinator species were found only in the wildflower habitat.…”
Section: Pollinationmentioning
confidence: 98%
“…Overall, this spillover may occur in conditions where agricultural habitats are subject to biodiversity-friendly management practices such as organic farming. Orford et al (2016) have shown that experimentally enhancing plant species diversity of conventional agricultural grasslands was associated to increases in functional diversity, species richness and abundance of pollinators. This, in turn, led to increased pollination efficiency of a wild phytometer species, the red campion (Silene dioica).…”
Section: Facilitation: Spillover Of Shared Pollinatorsmentioning
confidence: 99%